2007
DOI: 10.1080/03008200701331524
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Biology of Abdominal Aortic Aneurysms in Diabetes: Mechanisms Underlying the Negative Association

Abstract: Several case-control studies have shown a significant negative association between diabetes and abdominal aortic aneurysm (AAA). This interaction has the potential to further our understanding of these two diseases but has attracted little research. The changes seen in the walls of aneurysmal aortas include inflammation and the activation of proteolytic pathways resulting in loss of elastin and other structural proteins. In contrast, diabetes is associated with increased synthesis and reduced degradation of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 95 publications
0
64
0
6
Order By: Relevance
“…31 With aging and arteriosclerosis, the echostructure becomes more homogeneous, with an increase in collagen and elastin cross-links, making it less prone to dissection. 31 This process could be accelerated in individuals with hypercholesterolemia and elevated BMI, analogous to diabetes mellitus, which is associated with an increased synthesis and reduced degradation of the extracellular matrix, 33 an increased number of covalent cross-links between proteins, 34 and a reduced incidence of abdominal aortic aneurysms. 35 One could also speculate that lean persons, with less adipose tissue protecting the arteries from minor cervical traumas, might be more prone to developing CEAD as a result of increased vulnerability to such traumas.…”
Section: Underlying Mechanismsmentioning
confidence: 99%
“…31 With aging and arteriosclerosis, the echostructure becomes more homogeneous, with an increase in collagen and elastin cross-links, making it less prone to dissection. 31 This process could be accelerated in individuals with hypercholesterolemia and elevated BMI, analogous to diabetes mellitus, which is associated with an increased synthesis and reduced degradation of the extracellular matrix, 33 an increased number of covalent cross-links between proteins, 34 and a reduced incidence of abdominal aortic aneurysms. 35 One could also speculate that lean persons, with less adipose tissue protecting the arteries from minor cervical traumas, might be more prone to developing CEAD as a result of increased vulnerability to such traumas.…”
Section: Underlying Mechanismsmentioning
confidence: 99%
“…19 However, epidemiological studies have identified distinct differences in risk factors for aneurysmal versus atherosclerotic disease, a notable example being the protective effect of diabetes in AAA. 20 In addition, aneurysms are very rare in some locations that are particularly prone to atherosclerosis (eg, superficial femoral artery).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…33 It was supported that the reduced aortic wall stress seen in patients with DM may account for the decreased risk of AAA development. 34,35 The activation of proteolytic pathways and the increased inflammation seen in the walls of the aneurysmal aortas result in loss of elastin and other structural proteins. 35 In contrast, DM is associated with deposition of advanced glycation end products and increased vascular matrix synthesis.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…34,35 The activation of proteolytic pathways and the increased inflammation seen in the walls of the aneurysmal aortas result in loss of elastin and other structural proteins. 35 In contrast, DM is associated with deposition of advanced glycation end products and increased vascular matrix synthesis. 35 These differences may, in part, account for the negative correlation between DM and AAAs.…”
Section: Diabetes Mellitusmentioning
confidence: 99%